1998
DOI: 10.1016/s0163-6383(98)90015-7
|View full text |Cite
|
Sign up to set email alerts
|

Toddler regulation of distress to frustrating events: temperamental and maternal correlates

Abstract: Seventy-three mothers and their 18-month-old toddlers were observed in a series of laboratory procedures designed to assess relations among physiological arousal, frustration distress, emotion regulation and maternal interactive style. Physiological arousal was assessed using baseline measures of vagal tone and heart period. Distress was assessed across four separate episodes designed to elicit the intensity, frequency, duration and latency of the distress response to frustrating events. Regulation was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
216
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(233 citation statements)
references
References 31 publications
12
216
1
4
Order By: Relevance
“…Inter-rater reliability was calculated using Cohen's Kappas for behavioral strategies (fear = 0.73; positive affect = 0.84; frustration/anger = 0.70) and emotional expressions (fear = 0.70; positive affect = 0.80; frustration/anger = 0.78). This coding system is similar to those used in other studies of children coping strategies (Buss & Goldsmith, 1998;Calkins & Johnson, 1998;Diener & Mangelsdorf, 1999a;Parritz, 1996).…”
Section: Emotion Regulation Paradigm: Fear Positive Affect Frustratmentioning
confidence: 99%
“…Inter-rater reliability was calculated using Cohen's Kappas for behavioral strategies (fear = 0.73; positive affect = 0.84; frustration/anger = 0.70) and emotional expressions (fear = 0.70; positive affect = 0.80; frustration/anger = 0.78). This coding system is similar to those used in other studies of children coping strategies (Buss & Goldsmith, 1998;Calkins & Johnson, 1998;Diener & Mangelsdorf, 1999a;Parritz, 1996).…”
Section: Emotion Regulation Paradigm: Fear Positive Affect Frustratmentioning
confidence: 99%
“…A caregiver appears to provide ''scaffolding'' (e.g., Denham, Mason, & Couchoud, 1995) or structure that enables and fosters a child's emotional development. Examples of this phenomenon include (a) coregulation of infant emotion that is sensitive to the infant's (e.g., temperamental) needs, (b) coconstruction of emotion narratives by mother-child dyads that may serve as later emotion ''scripts'' for the child, and (c) maternal encouragement of autonomy as the child learns how to regulate independently of the mother (e.g., Calkins, 1994;Calkins & Johnson, 1998;Casey & Fuller, 1994;Denham, Renwick, & Holt, 1991;Eisenberg et al, 1999;Feldman, Greenbaum, & Yirmiya, 1999;Grolnick, Kurowski, McMenamy, Rivkin, & Bridges, 1998;Kobak, Cole, Ferenz-Gillies, Fleming, & Gamble, 1994;Oppenheim, Nir, Warren, & Emde, 1997;Roberts & Strayer, 1987).…”
Section: Other Emotion Regulation Processes: Normative Populationsmentioning
confidence: 99%
“…Each 10 second interval was also coded for previously identified behaviors established as indicators of emotion regulation (Calkins, 1996;Calkins & Johnson, 1998). These behaviors were coded for presence or absence in the 10-second intervals for both 30-second trials.…”
Section: Emotion Regulation Behaviorsmentioning
confidence: 99%
“…Calkins & Johnson (1998) demonstrated a negative relationship between the tendency to show distress during frustrating situations and certain regulatory behaviors. Similarly, Buss and Goldsmith (1998) observed that infants displayed a variety of emotion regulation behaviors during frustrating situations in an attempt to reduce negative affect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation